(untitled) (Research, Society and Development, 2022)
Objective: To compare the modeling capability of ProTaper Next and X-Gray rotary systems in simulated channels. Materials and methods: Twenty acrylic blocks (IM do Brasil, São Paulo, Brazil) were divided into 2 groups (n = 10): ProTaper Next (PTN) group and X-Gray (XG) group. The pre- and post-instrumentation images were superimposed in order to assess the canal centering ability with Adobe Photoshop CS5.1 (Adobe Systema, San José, USA). Results: The S Shapiro-Wil test was performed, in a distribution that resembles normal (p > 0.05) or not (p <0.05). The Protaper Next files had greater centralization capacity, whereas the X-Gray instruments had transport to the inner side of the first curvature and to the outer side in the second arrangement. Conclusion: 2 systems-rotation of the canals executed that conclude the 2 systems-rotators that project in the format, if able to use in canals.